Dosimetry Support of the Ukrainian-American Case-control Study of Leukemia and Related Disorders Among Chornobyl Cleanup Workers. Issue 4 (October 2015) - Chumak, Vadim; Drozdovitch, Vladimir; Kryuchkov, Victor; Bakhanova, Elena; Babkina, Natalya; Bazyka, Dimitry; Gudzenko, Natalya; Hatch, Maureen; Trotsuk, Natalya; Zablotska, Lydia; Golovanov, Ivan; Luckyanov, Nickolas; et al.
<x xml:space="preserve">Abstract</x> Abstract This paper describes dose reconstruction for a joint Ukrainian-American case-control study of leukemia that was conducted in a cohort of 110, 645 male Ukrainian cleanup workers of the Chornobyl (Chernobyl) accident who were exposed to various radiation doses over the 1986–1990 time period. Individual bone-marrow doses due to external irradiation along with respective uncertainty distributions were calculated for 1, 000 study subjects using the RADRUE method, which employed personal cleanup history data collected in the course of an interview with the subject himself if he was alive or with two proxies if he was deceased. The central estimates of the bone-marrow dose distributions range from 3.7 × 10−5 to 3, 260 mGy, with an arithmetic mean of 92 mGy. The uncertainties in the individual stochastic dose estimates can be approximated by lognormal distributions; the average geometric standard deviation is 2.0.